Job satisfaction of academics: does gender matter? - Taylor, Maria de Lourdes Machado (2014)
Academic work in higher education has been influenced by global trends such as accountability, massification and deteriorating financial support. Within this broader context, the performance of academic staff as teachers and researchers has an impact on student learning and implications for the quality of higher education institutions (HEIs). Therefore, satisfaction of academic staff is critical to the effective functioning of HEIs. This article reports on a study of academic career satisfaction in Portugal and gender differences with respect to academic job satisfaction. It found that male respondents in HEIs were in higher positions than women, but less so in private institutions. It also analysed some aspects of the professional context in which women and men work in order to explain similarities and/or differences in job satisfaction. The main difference was that women were less satisfied with personal and professional development, especially the balance between work and family.